Lipid-lowering and antioxidant effects of Polygonatum fermented liquor: a study on intestinal microbiota and brain–gut axis in mice - Yang, Xuan; Fang, Leyao; Shen, Junxi; Tan, Zhoujin; Zeng, Wenhong; Peng, Maijiao; Xiao, Nenqun (Frontiers in Nutrition, 2024)
Introduction This study aims to investigate the effects of Polygonatum fermented liquor (PFL) on improving lipid metabolism and oxidative stress in mice by regulating the gut microbiota. Methods Forty SPF-grade male Kunming mice were randomly divided into four groups: normal control group (NC), general liquor group (GC), fresh Polygonatum fermented liquor group (FPC), and nine-steam-nine-bask Polygonatum fermented liquor group (NPC). Each group was administered with sterile water, general liquor, fresh Polygonatum fermented liquor, and nine-steam-nine-bask Polygonatum fermented liquor, respectively, by gavage. The mice's liver, brain tissue, serum, and intestinal contents were collected. The indicators of oxidative stress in the liver, four blood lipid indicators, gamma-aminobutyric acid (GABA), and brain-derived neurotrophic factor (BDNF) levels in the brain tissue were measured, liver hematoxylin and eosin (HE) staining was performed, and the gut microbiota in the small intestine were analyzed using 16S rRNA second-generation sequencing technology. Results Compared with the NC group, the NPC group showed significantly increased liver glutathione peroxidase (GSH-Px) content in mice (p < 0.05), reduced number of lipid droplets in the liver cells, and increased GABA and BDNF content in the brain tissues. The NPC group regulated lipid metabolism by lowering low-density lipoprotein cholesterol (LDL-C) and increasing high-density lipoprotein cholesterol (HDL-C) content in the mouse serum. Gut microbiota analysis showed significant changes in the gut microbiota of mice in the FPC and NPC groups, with increased richness and species diversity. These two groups increased the abundance of beneficial bacteria such as Lactobacillus, unclassified Muribaculaceae, unclassified Bacilli, and uncultured Bacteroidales bacterium while reducing the abundance of harmful bacteria such as Candidatus Arthromitus, and Staphylococcus, with a particularly significant reduction in Staphylococcus (p < 0.05). It is speculated that the two types of PFL may exert lipid-lowering and antioxidant effects by modulating the abundance of these dominant bacteria. Further studies showed that various environmental factors are closely related to the dominant gut bacteria. Malondialdehyde (MDA) was significantly negatively correlated with Lactobacillus and unclassified Bacilli, superoxide dismutase (SOD) was significantly negatively correlated with Staphylococcus (p < 0.01) and significantly negatively correlated with Candidatus Arthromitus (p < 0.05), and HDL-C was significantly negatively correlated with Staphylococcus and Facklamia (p < 0.05). Discussion The two types of PFL chosen in this study may exert lipid-lowering and antioxidant effects by modulating the composition and function of the gut microbiota, providing guidance for the industrial application of Polygonatum.